CLINICAL FEATURES OF OTITIS MEDIA IN PATIENTS WITH HIV INFECTION - Sh.A., Alimova (Journal of Medical Genetics and Clinical Biology, 2024)
The work was carried out at the clinical base of the Bukhara State Medical Institute - and at the regional multidisciplinary clinical hospital. Analyzed data of examination and treatment of 75 patients from 18 to 60 years old, with ENT pathology against the background of HIV infection for the period from 2020-2021. Also examined were 30 non-HIV-infected patients of the same age and sex. All patients underwent a comprehensive examination, including otorhinolaryngological, clinical laboratory, bacteriological, and immunological studies. HIV-infected patients are characterized by frequent exacerbations of ENT diseases, in which 78.8% of patients were hospitalized due to the severity of the disease, and 21.2% of patients were treated in an outpatient setting. Severe and complicated forms of ENT disease occurred at a high frequency against the background of HIV infection, accounting for 23%. Of the complications that developed against the background of HIV infection, 13.4% were meningitis, 7.7% were brain abscesses, 1.9% were severe sepsis, and 9.6% were fatal.